Empowering physical activity through ‘Active Fun Play’ - Mohammad Haffizie, Malisa Haziqah; Teo , Boon Sian; Chin, Ngien Siong; Teng, Kie Yin; Ak Walter, Michelle Melini; Walter Lakun, Clarriechel (Jurnal Pendidikan Bitara UPSI, 2025)
Active Fun Play (AFP) is an interactive multi-approach combining Roblox platform with exercise games designed to support children with Autism Spectrum Disorder through an engaging, interactive and inclusive digital learning experience in physical activity. The AFP also incorporates real-world physical activity embedded with exercise games through immersive storyboards creating a seamless blend of virtual and physical world. This purpose of this innovation is to adopt an interactive multi-approach to empower a fun gamified system to help children with ASD to improve their motor skills by connecting their mind and body, encouraging them to plan and execute movements while responding to their environment. The AFP has been implemented within inclusive educational settings in schools which demonstrated a positive impact on the development of physical activity skills among ASD students. The AFP proves its value in inclusive education being more engaging, fun and interactive. Through its interactive capabilities, it provides a safe and stimulating environment where learners can learn and acquire vital physical activity skills at their pace by guaranteeing an enjoyable and accessible education experience for all.